Leadership communication - Barrett, Deborah J. (McGraw Hill, 2006)
Leadership Communication is a text to guide current and potential leaders in developing the communication capabilities needed to lead organizations effectively. It brings together managerial communication and concepts of emotional intelligence to create a new model of communication skills and strategies for corporate leaders. It begins with chapters on the core communication skills of developing strategy, analyzing an audience, writing all types of business documents and correspondence, and designing and delivering effective PowerPoint presentations - all from a leadership perspective. Then, it takes students through chapters on emotional intelligence, cultural literacy, meeting management, and team leadership, before concluding with chapters on internal and external organizational communication.